Human and Nature in Donny Dhirgantoro’s 5 cm: An Ecocritical Reading - Olivia Tedjowahyudi (Institute of Research and Community Outreach - Petra Christian University, 2022)
This research aims to analyze Donny Dhirgantoro’s novel, 5 cm, from the perspective of ecocriticism. It tries to investigate the roles of each setting and the portrayals of human-nature relationship in the narrative. The results indicate that there is a dichotomy of the city and mountain. City is depicted as the antagonist while mountain is the protagonist, taking the role of a mother. The narrative conveys nature as an autonomous entity with power to attack/ support the inhabitants. There is interdependency between nature and human being in the text. Nature needs human being to protect it while humans maintain their good relationship with the nature by keeping the rules and social norms around the setting in order to obtain the protection from nature. Despite the novel’s attempt to put nature as the more superior entity, the character’s decision at the end of the narrative shows that nature is still seen as a source of comforts to satisfy human’s needs.